2013
DOI: 10.1136/annrheumdis-2012-202315
|View full text |Cite
|
Sign up to set email alerts
|

Secondary analysis of APPLE study suggests atorvastatin may reduce atherosclerosis progression in pubertal lupus patients with higher C reactive protein

Abstract: Objective Participants in the Atherosclerosis Prevention in Paediatric Lupus Erythematosus (APPLE) trial were randomised to placebo or atorvastatin for 36 months. The primary endpoint, reduced carotid intima medial thickness (CIMT) progression, was not met but atorvastatin-treated participants showed a trend of slower CIMT progression. Post-hoc analyses were performed to assess subgroup benefit from atorvastatin therapy. Methods Subgroups were prespecified and defined by age (> or ≤15.5 years), systemic lupu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 40 publications
2
34
2
1
Order By: Relevance
“…In contrast, our patients showed a greater prevalence of active LN. Secondary analysis of the data reported by Schanberg et al [22,24] showed that atorvastatin may slow the progression of cIMT thickening only in a subgroup of pubertal patients with higher high-sensitivity C-reactive protein [23]. In contrast to our findings, Boros et al [27] found an increase in PWV, but no increase in cIMT or flow-mediated dilatation, among a cohort of children with SLE.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In contrast, our patients showed a greater prevalence of active LN. Secondary analysis of the data reported by Schanberg et al [22,24] showed that atorvastatin may slow the progression of cIMT thickening only in a subgroup of pubertal patients with higher high-sensitivity C-reactive protein [23]. In contrast to our findings, Boros et al [27] found an increase in PWV, but no increase in cIMT or flow-mediated dilatation, among a cohort of children with SLE.…”
Section: Discussioncontrasting
confidence: 90%
“…Likewise, Ghosh et al observed increased fibromuscular dysplasia (FMD) and cIMT in 60 Indian patients with SLE who showed impaired FMD and abnormal IMT [48]. Our group has a greater proportion of African American patients than other paediatric studies [22][23][24][25][26][27], and this may have affected the results.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Secondary analyses showed a trend in favor of atorvastatin for other CIMT endpoints. Post-hoc exploratory subgroup analyses showed a trend toward reduced CIMT progression in patients with high-sensitivity C-reactive protein (!1.5 mg/l) and in those who were postpubertal [18]. Results of these secondary and post-hoc analyses need to be taken cautiously as performing multiple comparisons increases the risk of type I error.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…The data supporting the use of statins specifically in SLE are also scarce and controversial. On one hand, statin use had no effect on the progression of subclinical atherosclerosis (assessed as progression of carotid intima-media thickness) in an unselected group of pubertal SLE patients [73], but, on the other hand, atorvastatin was effective in a subgroup of patients with elevated CRP [74]. Interestingly, statin use was associated with a decrease of SLE activity, but statins had no effect on measured proinflammatory/prothrombotic biomarkers [75].…”
Section: Reducing Side Effects Of the Treatmentmentioning
confidence: 99%